Significance and sustainability of communiversity at IIUM: a public history project - Mamat, Adilah Asyikin; Azmi, Afifah Thahirah; Adanan, Nuralia Sharmila; Abdullah Fauzi, Nurfariha Akmal Fawwazah; Mohd, Siti Hadija; Nazmi, Siti Naqibah Umairah (Akademi Tenggara Press, 2025)
This Public History research project explores the concept of Communiversity at IIUM, an initiative rooted in bridging academia with society. Using Public History methodology, this study examines the historical development, significance, and impact of Communiversity. Data gathered from qualitative interviews with key stakeholders reveal its long-term benefits, practical challenges, and the importance of student participation in ensuring its sustainability. The findings highlight Communiversity as a model for sustainable education, community transformation, and institutional collaboration. Moreover, this study situates Communiversity within the wider literature on community-university partnerships, emphasizing its role in nurturing mutual learning and contributing to the long-term development of both students and society.